Prevalence of Iron Deficiency Anemia among University Students in Hodeida Province, Yemen - Abdullah Ahmed Al-alimi; Salem Bashanfer; Mohammed Abdo Morish (Anemia)
Background. Iron deficiency anemia (IDA) is one of the most common types of nutritional anemia in the worldwide and considered a major public health problem in developing countries especially in Yemen. Therefore, this cross-sectional study was conducted to determine the prevalence and risk factors of IDA among apparently healthy Yemeni students at Hodeida University. Method. Five hundred blood samples (326 males and 174 females) were collected randomly from medical students at Hodeida University. Participants were subjected to different tests including complete blood counts (CBC), serum ferritin (SF), serum iron (SI), and total iron binding capacity (TIBC). Moreover, a questionnaire was designed to collect demographics, food and drink habits, and socioeconomic status. Result. The overall prevalence of IDA was 30.4%  (n=152), of whom 54.00% were females (n=82) and 46.0% were males (n=70). Students aged 20–22 years were found more anemic with prevalence 59.2% than students aged 17–19 years (25.0%) and 23–25 years (15.8%). Statistical analysis showed regularly having breakfast had significant (p < 0.001) role in preventing development of IDA compared with irregularly having breakfast. Infrequent consumption of vegetables/fruits; meat, fish, chicken; tea drinking; low household income; smoking and khat (Catha edulis) chewing showed a significant role (p < 0.001) in provoking of IDA, whereas consumption of coffee and cola showed insignificant influence (p=0.585; p=0.513) on IDA. Conclusion. This study revealed that the majority of university students, especially females, have IDA that might become worse by malnutrition, lifestyle habits, and lack of awareness. Our results suggest that IDA can be prevented by providing proper knowledge on the healthful diet, improved lifestyle, and harmful effect of IDA to the students.